Kelangsungan Hidup Larva Planula Acropora sp dalam Pemeliharaan Terkontrol Kepadatan yang Berbeda - Syafyudin Yusuf; Juniur Rangan; Esther Sandamanapa (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
The survival of coral larvae as early phase of coral life is very important for their viability in environmen. This research aims to determine the survival of Acropora sp planula at different densities intensive nursery, and also to khow the critical survival time of them.. This research method was used experiment in density of larvae were held in control laboratory. The planula were rearing ini small container 200 ml of water while the lavae density were used namely 0.5; 1.0, 1.5, 2.0 larvae / ml. The results indicated that survival rate for larvae of different densities (0.5 larvae/ml; 1.0 larvae/ml; 1.5 larvae/ml; 2.0 larvae/m) did not show any significant difference (P>0.05). the highest survival rate of planula larvae was in the treatment with a density of 1.5 larvae/ml and the lowest from a density of 2.0 larvae/ml, and the most larval mortality was in the first 12 hours of rearing, due to the degree of adaptation of larvae to the rearing water medium in all treatment units, then death coral larvae decreased exponentially. This research will be very useful for efforts to restore coral reefs sexually, so as to reduce the impact of exploitation of coral seedlings which are often taken for asexual coral reef restoration as is often done throughout the world's coral reefs.